Perceptions of health among school-aged children living in socially vulnerable areas in Sweden - Isma, Gabriella E.; Rämgård, Margareta; Enskär, Karin (Frontiers in Public Health, 2023)
According to the Convention on the Rights of the Child, all children have the right to health. Since good health is a decisive factor for children’s future, investing in children’s health is important, especially children from vulnerable areas. The purpose of this study was to investigate the perceptions of health among school-aged children from socially vulnerable areas. The study has an explorative mixed-method design with a participatory and inductive approach based on focus group interviews with children and youth leaders, respectively, at Multi-activity Centers in three of the vulnerable areas in Malmö Municipality, as well as results from the Multi-activity Centers’ own questionnaire. The data has been analyzed with inductive and deductive content analysis. The children and the youth leaders described health in terms of well-being, participation, and activity. Well-being included feeling good and safe, having a healthy body, and having fun by doing things together with friends and leaders. Participating in activities was described as having a feeling of involvement, being able to have an influence on the organization of the activities and participating on one’s own terms. The result of this study shows that participating in activities increases the child’s sense of well-being.